Golden lion tamarins, Leontopithecus rosalia (Linnaeus, 1766) in the Taquara Municipal Natural Park (Duque de Caxias, RJ): a southern extension of the known range - Burity, Carlos Henrique Freitas; Cruz, Leandro Duarte; Luz, Daniel Eduardo; Santos, Durval Silva; Campos, Devylson Costa; Rocha, Vera Lúcia; Conceição, Nelson Barroso; Pissinatti, Alcides (Neotropical Primates, 2007)
No abstract